Structural Relaxation in Polyanionic Sodium Fluorophosphate Glasses - Calahoo, Courtney; Petrovic, Jelena; Le, Quyen Huyen; Werner-Zwanziger, Ulrike; Zwanziger, Josef; Wondraczek, Lothar (Frontiers in Materials, 2019)
Structural heterogeneity is a common feature of all glasses, however, little is known about the underlying contributions of chemical fluctuations and modulations in free volume in concrete glass forming systems. In this investigation, we relate the dynamics of structural relaxation of (100-x)NaPO3–xAlF3 glasses to their heterogeneous structure as determined from multinuclear magnetic resonance spectroscopic analysis. For this, we evaluate differential scanning calorimetry (DSC) data using the integral isoconversional method to determine the variation in activation energy, Ea, of the glass transition as a function of temperature and conversion progress. Specific heat measurements from DSC allow for the determination of the effective size of the cooperatively rearranging region (CRR). From 31P, 19F and 27Al NMR, we observe that the introduction of AlF3 into the NaPO3 network increases the average connectivity (i.e., the number of heteronuclear Al—O—P bonds), rationalizing the higher Ea determined from the DSC measurements. We find highly constrained regions of Al(OP)4F2 with Al—F—Al cross-linking (high Ea) and, simultaneously, more flexible regions of phosphate chains containing P—F··(Na+)n bonds (low Ea); this results in a topologically and dynamically heterogeneous structure as evidenced by the increased variability in Ea with higher AlF3 content. The decreasing size of the CRR reflects the increased heterogeneity: at low AlF3 the CRR is large, while at high AlF3 (high heterogeneity), the CRR is significantly smaller (by a factor of 103). Finally, we relate the heterogeneity to other macroscopic properties, such as Tg and mechanical properties.